(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Information and Communication Technology has changed the operation and user information programs of public, special and academic libraries. Libraries are facing a piquant situation and unforeseen challenges in this age of information technology. This paper discusses the impact of ICT in library services and the study was conducted to investigate the awareness, skill and attitude towards ICT among the students of Govt. Saitual College.